Messianism and Astronomical Events during the First Four Centuries of Islam - David Cook (Université de Provence, 2000)
Messianism and astronomical events are interconnected from the very earliest period of Islam. Although we do not know whether the appearance of comets and supernovae influenced the Prophet Muhammad to believe that the end of the world was imminent as he was receiving the revelations of the Quran, the fact is that a great many apocalyptic and messianic movements during the following four centuries and afterwards were accompanied by astronomical phenomena. This article is designed to open students of Islam up to the possibility that celestial events are important for the study of these apocalyptic movements and are frequently useful in dating their exact beginnings since in many cases we lack information about the genesis of such movements.